First Attempts to Ban Chemical Weapons - N. I. Shilo (Вестник войск РХБ защиты)
First attempts to ban chemical weapons (CW) as a method of warfare have been made since the second half of the XIX century. At the beginning of the XX century, several legal documents – declarations, protocols and conventions, forbidding the use of poisons, poisonous weapons, poisonous and asphyxiating gases and means of their delivery, have been adopted at the international level. But all these documents, including the Hague Conventions of 1899 and 1907 and the 1925 Geneva Protocol, turned out to be useless and ineffective as a means of deterrence. They could prevent neither large-scale use of CW in World War I, nor their further development. Instead of the assistance to the prohibition of CW, in fact they assisted their legalization and further arms race. The article is dedicated to the history of first efforts to ban CW by international treaties. It describes in details the circumstances of the elaboration of these declarations, protocols and conventions in connection with other general security problems, their further adoption or breakdown. Special attention is paid to the attitude towards CW at the beginning of the XX century and their use as a means of pressure and propaganda.